2001
DOI: 10.1097/00061198-200112000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Follow-up of Initial 5-Fluorouracil Trabeculectomy in Primary Open-angle Glaucoma in Japanese Patients

Abstract: Trabeculectomy with 5-fluorouracil as an initial surgery in Japanese patients with primary open-angle glaucoma was effective for long-term control of glaucoma. However, the probability of late-onset bleb-related complications was not low in eyes with a functioning bleb, stressing the importance of constant care regarding bleb status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 52 publications
0
17
0
Order By: Relevance
“…12,24 Wong et al 12 reported the trabeculectomy survival with intraoperative 5-FU application to be 75.8% at 1 year and 65.8% at 3 years for the Asian patients in Singapore. The definition of success of that study was IOPo22 mmHg without additional medication or surgery.…”
Section: Discussionmentioning
confidence: 99%
“…12,24 Wong et al 12 reported the trabeculectomy survival with intraoperative 5-FU application to be 75.8% at 1 year and 65.8% at 3 years for the Asian patients in Singapore. The definition of success of that study was IOPo22 mmHg without additional medication or surgery.…”
Section: Discussionmentioning
confidence: 99%
“…With surgery, levels of IOP in the low teens, or even lower, are technically achievable, 20,21,[34][35][36][37] and that is independent of the IOP values prior to surgery. What determines IOP levels postoperatively are mainly the degree of surgical precision intraoperatively, the resistance to outflow posed by the scleral flap in trabeculectomy, at least initially.…”
Section: Sufficient Reduction Of Iopmentioning
confidence: 99%
“…What determines IOP levels postoperatively are mainly the degree of surgical precision intraoperatively, the resistance to outflow posed by the scleral flap in trabeculectomy, at least initially. In the long run, the degree of wound scarring 30 postoperatively and whether this has been manipulated by antimetabolites, 21,35 plays a role of paramount importance.…”
Section: Sufficient Reduction Of Iopmentioning
confidence: 99%
See 2 more Smart Citations